2007
DOI: 10.1075/is.8.3.09ber
|View full text |Cite
|
Sign up to set email alerts
|

Working with a robot

Abstract: Research on human-robot interaction has often ignored the human cognitive changes that might occur when humans and robots work together to solve problems. Facilitating human-robot collaboration will require understanding how the collaboration functions system-wide. We present detailed examples drawn from a study of children and an autonomous rover, and examine how children's beliefs can guide the way they interact with and learn about the robot. Our data suggest that better collaboration might require that rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Overall, we found that discouraging expressive language caused less-rational performance (λ = 0.51 for negative vs. λ = 0.58 for positive). This is in line with what might be expected and with previous work [31], [44], [45]. A participant will believe they will make better choices when encouraged, whereas a discouraged individual will make more mistakes.…”
Section: B Population Rationalitysupporting
confidence: 91%
“…Overall, we found that discouraging expressive language caused less-rational performance (λ = 0.51 for negative vs. λ = 0.58 for positive). This is in line with what might be expected and with previous work [31], [44], [45]. A participant will believe they will make better choices when encouraged, whereas a discouraged individual will make more mistakes.…”
Section: B Population Rationalitysupporting
confidence: 91%
“…As such, successful deployment of social robots requires a broader focus of analysis, in order to account for future user's attitudes, beliefs and expectations, and how they will impact human-robot interaction [8].…”
Section: Introductionmentioning
confidence: 99%